Ludność ukraińska na ziemi lubuskiej po II wojnie światowej = Ukrainian people in the Lubuskie region after world war II - Nowak-Małolepsza, Fatima (Zielona Góra: Lubuskie Towarzystwo Naukowe)
This article deals with a suburb of Zielona Góra populated by immigrants from Ukraine.These people settled in this area in 1947 during the ?Wisła? operation. The article describeshow these people adopted the Polish lifestyle and interacted with the Polish population. These changes had major influence on the state politics, which assimilated and unified the Ukrainian minority and kept them under strict political control.
Keywords: ziemia lubuska; akcja "Wisła"; przesiedlenia; Ukraińcy za granicą - Polska - 1944-1989; historia; po 1944 r.